Co-constructive Patient Simulation: A Learner-Centered Method to Enhance Communication and Reflection Skills. Issue 6 (December 2021) - Martin, Andrés; Weller, Indigo; Amsalem, Doron; Duvivier, Robbert; Jaarsma, Debbie; de Carvalho Filho, Marco Antonio
Abstract : Introduction: In simulation sessions using standardized patients (SPs), it is the instructors, rather than the learners, who traditionally identify learning goals. We describe co-constructive patient simulation (CCPS), an experiential method in which learners address self-identified goals. Methods: In CCPS, a designated learner creates a case script based on a challenging clinical encounter. The script is then shared with an actor who is experienced working as an SP in medical settings. An instructor with experience in the model is involved in creating, editing, and practicing role play of the case. After co-creation of the case, learners with no prior knowledge of the case (peers or a supervisor) interview the SP. The clinical encounter is followed by a group debriefing session. Results: We conducted 6 CCPS sessions with senior trainees in child and adolescent psychiatry. Topics that are difficult to openly talk about may be especially appropriate for the CCPS model—without overt guidance or solicitation, the scripts developed by learners for this series involved: medical errors and error disclosure; racial tensions, including overt racism; interprofessional conflict; transphobia; patient-on-provider violence; sexual health; and the sharing of vulnerability and personal imperfections in the clinical setting. Conclusions: Co-constructive patient simulation provides an alternative multistage and multimodal approach to traditional SP simulation sessions that can adapt iteratively and in real time to new clinical vicissitudes and challenges This learner-centered model holds promise to enrich simulation-based education by fostering autonomous, meaningful, and relevant experiences that are in alignment with trainees' self-identified learning goals. Abstract : Supplemental digital content is available in the text.